Lean status in Serbian enterprises - Milicevic, Dusan (2008)
Nowadays lean is acknowledged as rapidly growing concept, used by companies worldwide in order to eliminate all kinds of wastes, from excess movement to overproduction, and maximize profit, through sustainable business improvement.